Titin-Actin Interaction: PEVK-Actin-Based Viscosity in a Large Animal. (15th November 2011) - Chung, Charles S.; Bogomolovas, Julius; Gasch, Alexander; Hidalgo, Carlos G.; Labeit, Siegfried; Granzier, Henk L.
Abstract : Titin exhibits an interaction between its PEVK segment and the actin filament resulting in viscosity, a speed dependent resistive force, which significantly influences diastolic filling in mice. While diastolic disease is clinically pervasive, humans express a more compliant titin (N2BA:N2B ratio 0.5–1.0) than mice (N2BA:N2B ratio 0.2). To examine PEVK-actin based viscosity in compliant titin-tissues, we used pig cardiac tissue that expresses titin isoforms similar to that in humans. Stretch-hold experiments were performed at speeds from 0.1 to 10 lengths/s from slack sarcomere lengths (SL) to SL of 2.15 μm. Viscosity was calculated from the slope of stress-relaxation vs stretch speed. Recombinant PEVK was added to compete off native interactions and this found to reduce the slope by 35%, suggesting that PEVK-actin interactions are a strong contributor of viscosity. Frequency sweeps were performed at frequencies of 0.1–400 Hz and recombinant protein reduced viscous moduli by 40% at 2.15 μm and by 50% at 2.25 μm, suggesting a SL-dependent nature of viscosity that might prevent SL ``overshoot'' at long diastolic SLs. This study is the first to show that viscosity is present at physiologic speeds in the pig and supports the physiologic relevance of PEVK-actin interactions in humans in both health and disease.